Efficacy and safety of ferric carboxymaltose in correcting iron-deficiency anemia: a review of randomized controlled trials across different indications - Bailie, George R (Arzneimittelforschung, 2010)
Ferric carboxymaltose (FCM, Ferinject®) was effective and well tolerated in the treatment of iron-deficiency anemia (IDA) in nine, Phase III, randomized, controlled, multicenter trials in a diverse range of indications, including patients with inflammatory bowel disease (IBD), post-partum anemia (PPA) or abnormal uterine bleeding (AUB), chronic heart failure (CHF), non-dialysis-dependent chronic kidney disease (CKD) and those undergoing hemodialysis (HD).In most trials, patients received either FCM doses of ≤ 1000 mg, administered intravenously (i. v.) over ≤ 15 min. or oral ferrous sulfate (FeSulf) 325 mg (65 mg iron), three times daily (t.i.d.), or 304 mg (100 mg iron), twice daily (b.i.d.). In one trial, patients on HD received 200 mg i. v. of either FCM or iron sucrose (ISC), two-to-three times weekly. In a pilot study in patients with CHF and CKD, patients received 200 mg of FCM by push injection compared with 200 mg of ISC slow injection. FCM was usually administered until the patient’s calculated total iron replacement dose was achieved.Treatment with FCM improved indices of anemia (hemoglobin [Hb], ferritin and transferrin saturation [TSAT] values). In patients on HD with IDA secondary to CKD, FCM demonstrated comparable efficacy to ISC in achieving an increase in Hb. In patients with IBD or PPA, improvements in Hb levels were more rapid with FCM than with FeSulf. Patients with PPA receiving FCM compared with those receiving oral iron achieved an Hb rise ≥ 2.0 g/dl earlier (7 days compared with 14 days; p < 0.001), were more likely to achieve an Hb rise ≥ 3.0 g/dl at any time beginning at day 14 (86.3% compared with 60.4%; p < 0.001), and achieve an Hb > 12.0 g/dl at the end of the study (Day 42; 90.5% compared with 68.6%, p < 0.01). Serum ferritin increased in the i. v. FCM treatment group, but not in the oral iron group. Differences between groups were significant at each study interval. TSAT increased significantly at every interval in both groups; however, FCM-treated patients showed higher TSAT at each interval after the first week. FCM improved patient quality of life to an equivalent extent to oral FeSulf in patients with IBD or PPA, and to a greater extent than oral FeSulf in women with AUB. FCM also improved quality of life as well as functional symptoms and exercise capacity in patients with CHF. Safety data from more than 3000 patients showed that FCM was well tolerated. No safety concerns have been identified in breastfed infants of mothers receiving FCM. FCM is, therefore, an effective and well-tolerated option in the treatment of IDA.
Keywords: Anemia; Ferinject®; Ferric carboxymaltose, efficacy, safety; Intravenous iron; Iron deficiency